DAMPAK MEDIA SOSIAL TERHADAP PENGEMBANGAN KONSEP DIRI PADA REMAJA DI SMKS HUMANIORA PANTON LABU - Muhammad Khaidir (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2023)
ABSTRACT: This research is entitled The Impact of Social Media on Self-Concept Expansion toward Teenager at SMKS Humaniora Panton Labu, The objectives of this study how are students’ behavior in social media at SMKS Humaniora Panton Labu and the impact of social media on students self-concept expansion at SMKS Humaniora Panton Labu. The type of research used is qualitative design by field research, the sources of data used consist of primary data sources in the form of interviews, observations and documentation in the field of research, and secondary data sources in the form of books, journals and publications related to research problems. Data collection techniques are structured interviews, observation and documentation. The results of this study show students’ behavior in media social at SMKS Humaniora is quite varied, such as the use of social media as self-existence media by uploading photos or videos, as a source of inspiration and self-development for talent expansion and as a communication media with friends in cyberspace. The impact of social media on self-concept expansion toward students at SMKS Humaniora Panton Labu consists of two namely positive and negative. Most of positive self-concepts experienced by students at SMKS Humaniora such as raise self-confidence, able to recognize self-potential, more creative and innovative, easier to control emotions, brave to express opinions and grow up tolerance for differences. While negative self-concepts such as had low self-esteem, pessimistic, unsure of their own abilities and often comparing their failures with the other achievements.